2020
DOI: 10.3171/2019.11.spine191055
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic vertebral artery injuries in the geriatric population: a retrospective cohort study

Abstract: OBJECTIVETraumatic vertebral artery injuries (TVAIs) are a common finding in cervical spine trauma and can predispose patients to posterior circulation infarction. While extensive research has been conducted regarding the management and criteria for imaging in patients with suspected blunt vascular injury, little research has been conducted highlighting these injuries in the geriatric population.METHODSThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Prior work by Page and Josiah describes traumatic vertebral artery injuries in the geriatric population. 8 The differences in patient selection and arterial inclusion between their study and ours expand the understanding of geriatric BCVI. To identify patients, the authors of the previous study cross-referenced all traumatic cervical spine injuries with patients found to have a vertebral artery injury.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Prior work by Page and Josiah describes traumatic vertebral artery injuries in the geriatric population. 8 The differences in patient selection and arterial inclusion between their study and ours expand the understanding of geriatric BCVI. To identify patients, the authors of the previous study cross-referenced all traumatic cervical spine injuries with patients found to have a vertebral artery injury.…”
Section: Discussionmentioning
confidence: 83%
“…Of these injury mechanisms, the most common causes of BCVIs in adults were motor vehicle accidents, whereas geriatric patients more commonly presented due to falls from standing height. 7,8 With the population of both the United States and the international community aging rapidly, and 1 in every 5 people expected to be older than 65 years by 2030, 9 special attention should be given to the geriatric population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rarely, medical procedures requiring hyperextension of the neck, such as esophagogastroduodenoscopy, have been reported to result in VA dissection [27]. Significant VAI is more likely to occur in patients less than 65 years of age than in younger patients with the same injury severity score [7].…”
Section: Etiology and Diagnosis Of Vai In Cervical Spine Fracturesmentioning
confidence: 99%
“…Segment II travels through the subaxial transverse foramina to C2. Segment III courses posterolaterally in a tortuous course from the transverse foramen of C2 to the posterior arch of C1, which renders it particularly vulnerable to stretch and rotational injuries [6,7]. Segment IV crosses the dura at the foramen magnum and runs superiorly to meet the proximal basilar artery.…”
Section: Introductionmentioning
confidence: 99%